2018
DOI: 10.1093/ndt/gfy264
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after transcatheter aortic valve implantation and mortality risk—long-term follow-up

Abstract: Periprocedural AKI following TAVI is a strong risk factor for short-term as well as long-term mortality (up to 7 years). Therefore more effort is needed to reduce this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Similarly, Bagur et al showed that 9% suffered from AKI after TAVR, whereas SAVR was associated with an incidence of AKI in 26% [24]. These results could be of impact, in fact, AKI was associated with an increased risk of 30-day and long-term (up to seven years) mortality (42.3% versus 22.7% for seven-year mortality; HR 1.71 (95% CI 1.30-2.25)) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bagur et al showed that 9% suffered from AKI after TAVR, whereas SAVR was associated with an incidence of AKI in 26% [24]. These results could be of impact, in fact, AKI was associated with an increased risk of 30-day and long-term (up to seven years) mortality (42.3% versus 22.7% for seven-year mortality; HR 1.71 (95% CI 1.30-2.25)) [25].…”
Section: Discussionmentioning
confidence: 99%
“… 5 - 8 Acute kidney injury complicating TAVR is associated with a higher mortality risk during short- and long-term follow-up. 9 - 11 In most patients who develop AKI, kidney function recovers partially or completely. Nonetheless, mortality risk remains high.…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a well-known complication post invasive cardiac procedure [1]. In the past, contrast material was considered the main culprit.…”
Section: Introductionmentioning
confidence: 99%